1997
DOI: 10.1007/s004030050162
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of mouse contact hypersensitivity after treatment with antibodies to leukocyte function-associated antigen-1 and intercellular adhesion molecule-1

Abstract: We investigated the effects of the antibodies against the adhesion molecules leucocyte function associated antigen-1 (LFA-1) and intercellular adhesion molecule-1 (ICAM-1) on mouse allergic contact hypersensitivity. Mice were injected intraperitoneally with both antibodies before sensitization by an epicutaneous application of dinitrofluorobenzene (DNFB). Simultaneous administration of the antibodies induced suppression of ear swelling in the effector phase of contact hypersensitivity. To show the effect of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…We showed that treatment with anti-CD155 mAb dampened CHS. Treatment with anti-LFA-1 mAb has been reported to similarly inhibit the development of CHS (42). However, although LFA-1 also mediates a costimulatory signal that leads to Th1 development from naive CD4 + T cells, mice deficient in LFA-1 or treatment of mice with anti-LFA-1 mAb show impaired migration of T cells to draining lymph nodes (43), leading to overall T cell dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that treatment with anti-CD155 mAb dampened CHS. Treatment with anti-LFA-1 mAb has been reported to similarly inhibit the development of CHS (42). However, although LFA-1 also mediates a costimulatory signal that leads to Th1 development from naive CD4 + T cells, mice deficient in LFA-1 or treatment of mice with anti-LFA-1 mAb show impaired migration of T cells to draining lymph nodes (43), leading to overall T cell dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to studies in mice with cutaneous contact hypersensitivity and rheumatoid arthritis patients, IL-4, and IL-10 production in liver of our GVAD model was unaffected by anti-ICAM-1 therapy. [50][51][52] Hence, anti-ICAM-1 appears to selectively decreases IL-2 production and T-cell proliferation in different tissues and mammalian species. The impressive increase in the serum IgE levels (humoral GVHD) in this model are dependent on IL-4 (Howell, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of adhesion molecules has been shown to be an important element in the pathogenesis of CD. Also several molecules involved in antigen presentation, such as major histocompatibility complex molecules or co-stimulatory molecules, are thought to be essential in ACD [Murayama et al, 1997]. On keratinocytes and in the perivascular infiltrates of the CHS response, a marked induction of the intercellular adhesion molecule 1 (ICAM-1) is observed.…”
Section: Overview Of the Use Of Transgenic Mice Of Cell Surface Molecmentioning
confidence: 99%